Healthcare Data Governance Ecosystems: Balancing Privacy, Innovation, and Compliance in Real-World Evidence Platforms - Sharma, Piyushi (IPHO-Journal of Advance Research in Science And Engineering, 2025)
Healthcare systems increasingly rely on data. This data drives clinical operations and innovation advancement. Real-world evidence platforms have become central to modern healthcare delivery. This creates urgent needs for robust data governance frameworks. Ethical considerations in patient data management have evolved significantly. Dynamic consent models now enable patients to maintain ongoing control. They can manage their information actively. Traditional consent frameworks prove inadequate for contemporary healthcare environments. Regulatory compliance presents complex challenges. These challenges span multiple jurisdictions. The Health Insurance Portability and Accountability Act establishes foundational standards in the United States. However, international regulations add layers of complexity. The General Data Protection Regulation is one example. Algorithmic bias in healthcare algorithms raises concerns. These concerns involve fairness and equity. Collaborative stewardship models enable multi-institutional data sharing. They preserve institutional autonomy at the same time. Federated governance architectures support interoperability. They do not compromise data control. Real-world evidence platforms aggregate diverse data sources. They generate meaningful insights from this aggregation. Privacy-preserving technologies offer solutions. They balance innovation needs with privacy protection. Differential privacy represents one promising technical approach. Federated learning represents another. The European Health Data Space demonstrates emerging regulatory frameworks. These frameworks address health data governance specifically. Healthcare organizations must navigate multiple dimensions simultaneously. These include ethical principles, regulatory requirements, and technological capabilities